2017
DOI: 10.32870/cys.v0i30.6833
|View full text |Cite
|
Sign up to set email alerts
|

Conectividad y desigualdad digital en Jalisco, México

Abstract: Este trabajo explora el estado que guarda el fenómeno de la desigualdad digital, medido en términos de conectividad, en el contexto del estado de Jalisco, una entidad de la República Mexicana, cuyos niveles de desarrollo y bienestar social se ubican en el tercio superior dentro del país, pero en el que campean también importantes indicadores de pobreza y desigualdad. El análisis se elabora tomando en consideración las tendencias generales que imperan en el desarrollo de las TIC a nivel global y nacional.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Mariscal (2005) investigated the issues of the digital divide in Mexico and claimed that the social capital issue is one of the useful factors to reduce the digital divide in terms of ICT access. Similarly, in Arredondo Ramírez (2017), digital connectivity was found as one of the key indicators of digital inequality in the state of Jalisco (in Mexico). In another study, Rallet and Rochelandet (2007) explored the impact of ICT to create the digital inequalities in different context like developed country, developing country, urban or rural areas, and so on and highlighted two issues of creating digital divide: uses of ICT, and regional discrimination due to the network support; while Nemer et al (2013) showed how the materiality of digital artifacts contributes to digital inequalities in Brazil’s urban areas.…”
Section: Related Workmentioning
confidence: 87%
“…Mariscal (2005) investigated the issues of the digital divide in Mexico and claimed that the social capital issue is one of the useful factors to reduce the digital divide in terms of ICT access. Similarly, in Arredondo Ramírez (2017), digital connectivity was found as one of the key indicators of digital inequality in the state of Jalisco (in Mexico). In another study, Rallet and Rochelandet (2007) explored the impact of ICT to create the digital inequalities in different context like developed country, developing country, urban or rural areas, and so on and highlighted two issues of creating digital divide: uses of ICT, and regional discrimination due to the network support; while Nemer et al (2013) showed how the materiality of digital artifacts contributes to digital inequalities in Brazil’s urban areas.…”
Section: Related Workmentioning
confidence: 87%
“…The studies (which are, henceforth, referenced by their number and can be consulted in Appendix), involved the participation of Latin American research centers (78.51%) from Mexico (studies 1, 8,11,13,14,18,31,34,35,42,46,48,51,58,60,63,67), Colombia (3,4,6,10,3 0,32,44,45,47,53,66), Brazil (16,17,22,33,39,55,64,65,68), Argentina (19,21,37,40,56,70), Chile (26,27,29,52,54), Peru (20,50), Uruguay (7,61), Bolivia (5,28), Ecuador (57), Costa Rica (69), Nicaragua (43), Dominican Republic (9) and Venezuela (36). In addition, albeit to a lesser extent, research centers from the United States (5.06%), Cana...…”
Section: Research Overviewmentioning
confidence: 99%
“…The geographical areas covered in the studies (countries that have been the study area of research studies) were Argentina (19,21,37,40,56,70), Bolivia (5,28), Brazil (16,17,22,33,39,55,64,65,68), Chile (26,27,29,52,54), Colombia (3,4,6,10,30,32 ,44,45,47,53,66), Costa Rica (69), Ecuador (57), Mexico (1,8,11,13,14,18,31,34,35,42,46,48,51,58,60,63,67), Nicaragua (43), Peru (20,50), Dominican Republic (9), Uruguay (7,61), and Venezuela (36); in addition, comparative studies simultaneously referred to several Latin American countries or addressed Latin America generally (2, 12,15,…”
Section: Research Overviewmentioning
confidence: 99%